Propriedades e características dos documentos em arquivos pessoais: uma revisão da literatura - Santana, Renata Lopes de (2019)
The present study aims to bring reflections concerning the multiplicity of perspectives of the concept of document in Personal Archives. In view of the diverse social uses of the document, Personal Archives are of fundamental importance for the guarding and safeguarding of the memory of groups, communities and individuals. Thus, with the advent of information and communication technology, we understand that the concept of a document promotes reflections mainly regarding its genesis and context of use. Therefore, in the document definition itself, it presents profound nuances of theoretical conceptions, as in the case of an archival document and an archival document, terms that are frequently used. However, when referring to personal documents, they keep what is convenient, what is selected by the titleholder of the collection, as the one who wishes to remain in memory of his life story for posterity. Our general objective is to analyze the main concept (s) of Document in Personal Archives that can better reflect its importance and functionality in the informational scenario. Thus, at first, we talked about the various concepts of the document, then we approach the characteristics belonging to the personal archives, reporting the importance of the binomial information and support, as main elements for the identity construction of the personal collections, in addition, we dialogue about personal archival documents, citing from their formation and construction process, until we report some examples of personal documents. Finally, we reflect the relevance of the documental conceptualization of artifacts, documents and personal materials, corroborating studies in the scientific field, Information Science, Archivology and other areas of knowledge.